Kemitraan Antar Aktor dalam Usaha Pengelolaan Ikan Air Tawar (Studi Kasus di Poklahsar Mina Rejeki Kalilondo Kelurahan Sidorejo Kidul Kecamatan Tingkir Kota Salatiga) - Nurul Mardiyah; Kushandajani . (Journal of Politic and Government Studies, 2019)
Local governments and their devices have a fundamental task in empowering their communities. Thus, the Government device, especially the regional office has a major in empowering communities in the region. Implementation of this empowerment requires a partner or cooperation from several Parties (stakeholders), given that the empowerment group is Poklahsar Mina Rejeki Kota Salatiga can thrive. This research aims to know the stakeholders who are involved in running a partnership with Poklahsar Mina Rejeki and analyze how the pattern of the partnership that occurred between Poklahsar Mina Rejeki and Dinas-Office of Salatiga City.The research method used is qualitative descriptive with the technique of data retrieval through interviews, observations and document study. The Data obtained is then analyzed by using source triangulation by comparing and checking the degree of information trust obtained in different time and tools. The triangulation technique of the source uses primary data from observation and interviews, as well as secondary data in the form of related documents.The results revealed: 1) actors involved in the partnership Poklahsar Mina Rejeki Kota Salatiga in the effort to manage freshwater fish that is the fishery area of the agricultural service of Salatiga City, Dinas Cooperative and UKM Kota Salatiga and Bapelibangda of Salatiga City. The involvement of some stakeholders helped the mechanism to run actively and was an early model of realizing good management. 2) The form of partnership that occurred between Poklahsar Mina Rejeki with Dinas-Dinas is partnering in terms of facilitation of training, coaching, bazar and capital loan. Fisheries field of the Agriculture Department of Salatiga City has a role in the training facilitation that has been created by Bappeda program. Bappeda received financial assistance for the development of the local economy and the implementation is the Agriculture Department of Fisheries. While the Department of Cooperatives and SMESprovide facilitation of bazaar, training and capital. The capital by Poklahsar Mina Rejeki in the personal name is not on behalf of the group.It is recommended that actors involved often conduct training that can improve the community empowerment, and the participation of the community in Poklahsar Mina Rejeki is not decreased.Keywords: mapping actors, stakeholders, forms of partnership,